Comparative responses of tracheal spirals and parenchymal strips to histamine and carbachol in vitro. - Drazen, J M (1978)
The responses of isolated guinea pig tracheal spirals and parenchymal strips to histamine and carbachol were compared. The parenchymal strip, a 1.5 x 1.5 x 20-mm strip cut from the periphery of the lung, constricted at a lower dose and had a larger maximal response to histamine than to carbachol. In contrast, the response of the tracheal spiral to equimolar doses of histamine or carbachol was the same. The responsiveness of both muscle strips to histamine was decreased by treatment with the H1 receptor antagonist mepyramine (0.1 micrometer), and the response to carbachol was blocked by treatment with atropine (0.1 micrometer). Indomethacin (3 micrometer), cimetidine (1 micrometer), propranolol (10 micrometer), and N-ethoxycarbonyl-2-ethoxy-1,2-dihydroquinoline (EEDQ) (4 micrometer) did not alter the differential response of the two strips to histamine and carbachol. The differential response of parenchymal strips with many, few, or no conducting airways and blood vessels was identical, suggesting that the contractile element is alveolar duct smooth muscle or alveolar contractile elements. This differential pharmacologic response in vitro is consistent with the in vivo observation that histamine causes more peripheral airway constriction than does acetylcholine.